Pengaruh Islamic Corporate Governance, Risiko Pembiayaan dan Efisiensi Operasional terhadap Kinerja Zakat Bank Pembiayaan Rakyat Syariah - Rury Risla Hasturi (Fakultas Ekonomi dan Bisnis, 2024)
This study aims to examine the influence of Islamic Corporate Governance, financing risk, and operational efficiency on zakat performance in Bank Pembiayaan Rakyat Syariah (BPRS). This quantitative explanatory research utilized secondary data from fourth quarterly reports and corporate governance implementation reports. The research objects is Bank Pembiayaan Rakyat Syariah (BPRS) that are registered with the Otoritas Jasa Keuangan (OJK) in Indonesia 2023. The 32 companies sample was obtained using purposive sampling techniques. Islamic Corporate Governance was measured by the ICG disclosure score, financing risk by Non Performing Financing (NPF), operational efficiency by Operating Expenses to Operating Income ratio (BOPO), and zakat performance by Zakat Performance Ratio (ZPR). The analysis uses multiple linear regression using SPSS 23 software. Data were analyzed through descriptive statistics, classical assumption tests, and multiple linear regression. The results indicated that the independent variables collectively explained 70% of zakat performance, while 30% was influenced by other variables not included in the study. The t-test results showed a probability value 0.488 for ICG, 0.00 for NPF, and 0.018 for BOPO. These result suggest that Islamic Corporate Governance measured by ICG disclosure score does not significantly affect zakat performance (ZPR), whereas financing risk (NPF) and operational efficiency (BOPO) do have a significant impact on zakat performance (ZPR).
Repo 16 Juli 2026_Rudy K Finalisasi 16 Juli 2026_Yudi
Keywords: Islamic Corporate Governance; financing risk; operational efficiency; zakat performance